Hypopituitarism in primary haemochromatosis; recovery after iron depletion. Issue 835 (May 1995) - Gama, R.; Smith, M. J.; Wright, J.; Marks, V.
Abstract : We report a case of primary haemochromatosis complicated by anterior hypopituitarism which recovered after aggressive venesection therapy. Reversal of anterior hypopituitarism in haemochromatosis following iron depletion has not been previously described.